p5RHH nanoparticle-mediated delivery of AXL siRNA inhibits metastasis of ovarian and uterine cancer cells in mouse xenografts - Mills, Kathryn A. (Sci Rep, 2019)
Ovarian and uterine serous cancers are extremely lethal diseases that often present at an advanced stage. The late-stage diagnosis of these patients results in the metastasis of their cancers throughout the peritoneal cavity leading to death. Improving survival for these patients will require identifying therapeutic targets, strategies to target them, and means to deliver therapies to the tumors. One therapeutic target is the protein AXL, which has been shown to be involved in metastasis in both ovarian and uterine cancer. An effective way to target AXL is to silence its expression with small interfering RNA (siRNA). We investigate the ability of the novel siRNA delivery platform, p5RHH, to deliver anti-AXL siRNA (siAXL) to tumor cells both in vitro and in vivo as well as examine the phenotypic effects of this siRNA interference. First, we present in vitro assays showing p5RHH-siAXL treatment reduces invasion and migration ability of ovarian and uterine cancer cells. Second, we show p5RHH nanoparticles target to tumor cells in vivo. Finally, we demonstrate p5RHH-siAXL treatment reduces metastasis in a uterine cancer mouse xenograft model, without causing an obvious toxicity. Collectively, these findings suggest that this novel therapy shows promise in the treatment of ovarian and uterine cancer patients.